RISK ANALYSIS OF ROOF FALL AND PREDICTION OF DAMAGED REGIONS AT RETREAT LONGWALL COAL MINING FACE - Sajjad Aghababaei; Gholamreza Saeedi; Hossein Jalalifar (Rudarsko-geološko-naftni Zbornik, 2020)
This study presents a model based on rock engineering systems (RES) to evaluate the risk of roof falls and determine damaged regions, using recorded roof falls, prior to mining with a retreat from a longwall face. In this regard, a case study was considered to examine the model. The results showed that the level of determined risk has an acceptable correlation with the special roof fall (SRF), with R-squared value (R2) equal to 0.792 for all estimated vulnerability indexes (VIs) in considered longwall panels. By investigating and comparing the evaluated values of VI in considered panels and their corresponding recorded roof falls, damaged regions were distinguished from undamaged regions. Based on these investigations, four classes including safe, moderate, danger, and critical regions were determined to identify the safe and damaged regions prior to the mining operation. The results of the research showed that the identification of damaged regions is feasible to provide a detailed operation plan to control roof falls in longwall mining faces through the developed approach. The RES-based model could be used for the same conditions and the presented methodology could be applied to other parts in underground coal mines.